2009
DOI: 10.1111/j.1447-0594.2008.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Fall risk factors in elderly patients with cognitive impairment on rehabilitation wards

Abstract: Background: Confusion and cognitive impairment, are risk factors for falls in hospital. Evidence for reducing falls in cognitively-impaired patients is limited and to date no intervention has consistently been shown to reduce falls in this group of patients. We explored characteristics associated with falls in cognitively-impaired patients in a rehabilitation setting. Methods:In a prospective observational study, 825 consecutive patients were studied. Patient characteristics were assessed on admission. Factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 25 publications
3
35
1
3
Order By: Relevance
“…Significant fall predictors for people with AD or other dementias include diagnosis of Lewy body disorder, a history of falls or recurrent falls in the previous 12 mo, symptomatic orthostatic hypotension, abnormal gait or balance score, impaired vision, and depression score (Allan et al, 2009;Harlein, Dassen, Halfens, & Heinze, 2009;Vassallo et al, 2009). Increased levels of physical activity and younger age have been reported to be protective factors against falls for people with AD (Allan et al, 2009).…”
Section: Background Literaturementioning
confidence: 99%
“…Significant fall predictors for people with AD or other dementias include diagnosis of Lewy body disorder, a history of falls or recurrent falls in the previous 12 mo, symptomatic orthostatic hypotension, abnormal gait or balance score, impaired vision, and depression score (Allan et al, 2009;Harlein, Dassen, Halfens, & Heinze, 2009;Vassallo et al, 2009). Increased levels of physical activity and younger age have been reported to be protective factors against falls for people with AD (Allan et al, 2009).…”
Section: Background Literaturementioning
confidence: 99%
“…Los estudios proponen y utilizan la rehabilitación, pero sigue siendo un reto que se complica con la medicación, factor importante del origen de éstas (43,57), pero pueden reducirlas mediante la gestión de la hipotensión ortostática, la depresión y el fomento de la actividad física (41). Investigar sobre un programa multifactorial que contenga diversas intervenciones puede reducirlas y prevenirlas (52,58).…”
Section: Discussionunclassified
“…One of the most important parameters to the LLLT is the wavelength, which can determine the depth of penetration and absorption, thus their effects. Since longer wavelengths are absorbed into the deeper layers of biological tissue 31 , and in the present study the aim was to reach the muscle tissue by stimulating the proprioceptive components 2,3,6 , it was chosen infrared 830 nm wavelength. Similar to the wavelength used by Almeida et al 32 , comparing the 830 nm to 660 nm, but found that both wavelengths promoted increased peak power and delayed fatigue of the biceps muscle.…”
Section: Discussionmentioning
confidence: 99%